O Moinho Satânico Chileno: a mercantilização da vida aprofundada pela lógica neoliberal - Machado, Fernanda Milena Alves (2024)
This dissertation proposes to debate neoliberalism from three perspectives: its form of ascension in the economic, political and social system, as a phase of accumulation based on financialization; its consequences for the social weave and the way in which the tentacles of this system paralyze society, preventing the liberation from its bonds. In view of the analysis of the transformations of the international monetary-financial system that laid the groundwork for the emergence of the neoliberal and financialized economic model, the unfolding of the value form configures a common thread, by stimulating the preponderance of finance in the political economy, in such a way that the impacts of the relationship between neoliberalism and financialization at the global and local levels, they are essential aspects to understand how the deterioration of the Chilean social fabric occurs, to which are added the legacies of the dictatorship, which were not completely modified during the subsequent governments. The social movements that have taken place since the 2000s exhibit the extent of such weariness, and the constituent process, as we understand it, is the materialization of a social exhaustion. Given the absence of a popular consensus, we discuss some notes about the limitations and advances that the movement of capital imprints on social reaction.